PERTUMBUHAN DIAMETER DAN TINGGI POHON SUNGKAI (Peronema Canescens Jack) UMUR 27 TAHUN DI HUTAN TANAMAN POLITEKNIK PERTANIAN NEGERI SAMARINDA - Herijanto Thamrin (JURNAL AGRIMENT, 2020)
Forests are one of the great natural resources of benefit to human welfare. Forests are also the basic capital of national development. As the basic capital of national development, the forest must be preserved so that the benefits of this forest will not only be enjoyed now, but for generations to come. Therefore, these forest resources need to be managed properly and appropriately so that the benefits and results can be optimal and sustainable. The purpose of this research was to find out the growth of the diameter and height of sungkai plants (Peronema canescens) aged 27 years in the Forest of Agricultural Polytechnic plants of Samarinda State. The expected result of this research is as an information material to the relevant parties as a consideration for the management of sungkai plants in the future. This research was carried out in the campus area of Samarinda State Agricultural Polytechnic. The material used is a 27-year-old sungkai (Peronema canescens) tree as many as 144 trees that were carried out for 3 (three) months, namely in October to December 2019. Diameter Measurement using Phiband and Height using Clinometer and tools in the form of pole / stick along 4 m. The results obtained are processed with simple statistics and analyzed using descriptive methods. Based on the results of processing and analysis of data that has been done, it can be concluded that the planting diameter of plants sungkai age 27 years in the area of Agricultural Polytechnic samarinda varies greatly with an average diameter of 17.42 cm, where plants with large diameters grow on the edge of the area and small ones are in the middle of the area. While the growth of sungkai plant height is relatively uniform with an average height of 20.19 m. The advice given from the results of this study is that there needs to be maintenance especially for looting because the growing space is less than ideal anymore. This can be seen by the related header of such plants in so difficult to distinguish the tip of the header from each other